2017
DOI: 10.5603/gp.a2017.0012
|View full text |Cite
|
Sign up to set email alerts
|

Manual vs. computer-assisted sperm analysis: can CASA replace manual assessment of human semen in clinical practice?

Abstract: Objectives: The aim of the study was to check the quality of computer-assisted sperm analysis (CASA) system in comparison to the reference manual method as well as standardization of the computer-assisted semen assessment. Material and methods:The study was conducted between January and June 2015 at the Andrology Laboratory of the Division of Infertility and Reproductive Endocrinology, Poznań University of Medical Sciences, Poland. The study group consisted of 230 men who gave sperm samples for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Reference values of up to 25% and 10th percentiles from 3% to 5% normomorphic spermatozoa have been shown in studies regarding fertility, in vitro fertilisation and in vivo fertility and for fertile male populations (Haugen, Egeland, & Magnus, ). Other studies reported 8% to 9% morphologically normal spermatozoa in healthy subjects (Paasch et al, ) and 4.8% and 3% in ejaculate samples of patients attending a fertility clinic (Henkel et al, ; Talarczyk‐Desole et al, ) after Papanicolaou staining.…”
Section: Discussionmentioning
confidence: 93%
“…Reference values of up to 25% and 10th percentiles from 3% to 5% normomorphic spermatozoa have been shown in studies regarding fertility, in vitro fertilisation and in vivo fertility and for fertile male populations (Haugen, Egeland, & Magnus, ). Other studies reported 8% to 9% morphologically normal spermatozoa in healthy subjects (Paasch et al, ) and 4.8% and 3% in ejaculate samples of patients attending a fertility clinic (Henkel et al, ; Talarczyk‐Desole et al, ) after Papanicolaou staining.…”
Section: Discussionmentioning
confidence: 93%
“…Although much progress has been made, CASA results are still subject to high inter-observer variability due to a lack of frequent and uniform standardization of CASA techniques, CASA's requirement for precise recalibration (suggested at 6-month intervals), and the need to consistently retrain laboratory staff when software updates are implemented. Additionally, variations in technician proficiency in other laboratory techniques (e.g., pipetting, loading the counting chamber) can contribute to variations in CASA results [15,43]. Although SA performed by a technician highly trained in the use of CASA has shown improved precision over manual methods [44], proper operation of this technology requires constant supervision and calibration, which is costly and inefficient [12].…”
Section: Computer-assisted Sperm Analysismentioning
confidence: 99%
“…Chemiluminescence, which measures light emitted by a reaction between chemical reagents and ROS in the sample, is widely used in the evaluation of seminal ROS, but has several limitations. First, chemiluminescence cannot measure ROS in frozen samples [15]. Second, due to the 800 µL sample requirement to run the test, patients with low semen volume cannot be evaluated.…”
Section: Oxidative Stress Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this sceptical voice is not constrained to issues of count. A recent study by Talarczyk-Desole et al (2017) suggests that although there are positives to using CASA, the time CASA-Morph takes to perform a sperm morphology assessment, as well as the differences shown between CASA-Mot results and trained laboratory staff, mean that there are still improvements needed before CASA is routinely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%